No alignment of cattle along geomagnetic field lines found - Hert, J; Jelinek, L; Pekarek, L; Pavlicek, A (Journal of comparative physiology. A, Neuroethology, sensory, neural, and behavioral physiology, 2011)
This paper presents a study of the body orientation of domestic cattle on free pastures in several European states, based on the Google satellite photographs. In sum, 232 herds with 3,412 individuals were evaluated. Two independent groups participated in our study and came to the same conclusion that in contradiction to the recent findings of other researchers, no alignment of the animals and of their herds along geomagnetic field lines could be found. Several possible reasons for this discrepancy should be taken into consideration: poor quality of Google satellite photographs, difficulties in determining the body axis, selection of herds or animals within herds, lack of blinding in the evaluation, possible subconscious bias, and, most importantly, high sensitivity of the calculated main directions of the Rayleigh vectors to some kind of bias or to some overlooked or ignored confounder. This factor could easily have led to an unsubstantiated positive conclusion about the existence of magnetoreception.
Keywords: skot; Cattle; Behavior, Animal; chování zvířat; orientace; Animals; elektromagnetická pole; Orientation; zvířata; Electromagnetic Fields